Parasitic nematodes of Pool Frog (Pelophylax lessonae) in the Volga Basin - Igor V. Chikhlyaev (Revista MVZ Córdoba, 2019)
Objetive. Present a modern review of the nematodes fauna of the pool frog Pelophylax lessonae (Camerano, 1882) from Volga basin populations on the basis of our own research and literature sources analysis. Materials and methods. Present work consolidates data from different helminthological works over the past 80 years, supported by our own research results. During the period from 1936 to 2016 different authors examined 1460 specimens of pool frog, using the method of full helminthological autopsy, from 13 regions of the Volga basin. Results. In total 9 nematodes species were recorded. Nematode Icosiella neglecta found for the first time in the studied host from the territory of Russia and Volga basin. Three species appeared to be more widespread: Oswaldocruzia filiformis, Cosmocerca ornata and Icosiella neglecta. For each helminth species the following information included: systematic position, areas of detection, localization, biology, list of definitive hosts, the level of host-specificity. Conclusions. Nematodes of pool frog, excluding I. neglecta, belong to the group of soil-transmitted helminthes (geohelminth) and parasitize in adult stages. Some species (O. filiformis, C. ornata, I. neglecta) are widespread in the host range. The latter two are able to reach high invasion indices and also to be the background parasites of the pool frog. It happens due to these nematode species life cycle specificity and the long-term connection of the amphibian with water.